DASHMM: Dynamic Adaptive System for Hierarchical Multipole Methods (Communications in Computational Physics, 2018)
We present DASHMM, a general library implementing multipole methods(including both Barnes-Hut and the Fast Multipole Method). DASHMM relies on dynamicadaptive runtime techniques provided by the HPX-5 system to parallelize theresulting multipole moment computation. The result is a library that is easy-to-use,extensible, scalable, efficient, and portable. We present both the abstractions definedby DASHMM as well as the specific features of HPX-5 that allow the library to executescalably and efficiently.